Molecular analyses of flightless weevils Chiloneus from Sicily and adjoining islands revealed new synonymy (Coleoptera: Curculionidae). Issue 1 (1st January 2021) - De Biase, A.; Colonnelli, E.; Baviera, C.; Bellò, C.; Casalini, R.; Corso, A.; La Marca, A.
Abstract: The trophic ecology of Chiloneus weevil species from Sicily was unknown until recently when the host plant of these closely related species was discovered. The opportunity to collect many samples of these elusive species allowed us to re-evaluate the morphology and the genetic relationships among the three closest of the four species inhabiting Sicily and the adjoining islands. We analysed a fragment of the cox1 mitochondrial gene of adult specimens collected from the host plant Drimia pancration in Sicily, Pantelleria, Pelagie Islands and Malta to study the population structure and the relationships among the different nominal species known so far. Both morphological and genetic results suggest that the previous three species are actually two species with disjunct distribution, for which the new synonymy C. hoffmanni (González, 1970) (= C. solarii Pesarini, 1970, syn. nov.) is established. Chiloneus meridionalis (Boheman, 1840) inhabits the main island of Sicily and Pantelleria island, while C. hoffmanni is restricted to Malta and Pelagie islands. Adults of the two species are very similar in general appearance but still distinguishable by a set of well-established characters presented here in a key to their identification. The genetic approach provided evidence of a certain degree of structure of the genetic variation within the two species that would be worth addressing from a phylogeographic perspective in future work. urn:lsid:zoobank.org:pub:1F03BA05-B7A9-44B7-8225-321174A1E3FB